Influence of Customary Law on Marriage Dispensation Post-Law No. 16 of 2019 Amendment to Law No. 1 of 1974 - Mudar, Andi Nadir; Abdullah, Asnawi; Lahmudinur, Lahmudinur (Institute of Education and Social Research, 2024)
The influence of customary law on the Marriage Dispensation Phenomenon after the issuance of Law No.16 of 2019 at the Andoolo Religious Court is a very important thing to do to determine the objective conditions of the effect of customary law on the phenomenon of Marriage Dispensation, the factors that cause the applicant to apply for dispensation of marriage and the reasons for the Judge's consideration and its impact. This research is a qualitative descriptive study, using the juridical-empirical approach method, primary and secondary data sources through observation, interviews, reviewing various books, archives of the KUA marriage refusal, archives of decisions/decisions of the Andoolo Religious Court, websites and several related and relevant regulations. with this writing. The results showed that the effect of customary law on the objective conditions of marriage dispensation after the issuance of Law No. 16 of 2019 greatly affects the increasing number of cases of dispensation of marriage, the factors causing dispensation of marriage include; already pregnant, influenced by customs, dropped out of school, determined the day of marriage, forced marriage, the reason for the judge's consideration; maintain the status of the party in the eyes of the community, the situation is urgent, prevents harm. Impact of Marriage Dispensation; have a positive and negative impact.